Variable stars in the Bochum Galactic Disk Survey. Issue 7 (10th September 2015) - Kaderhandt, L.; Barr Domínguez, A.; Chini, R.; Hackstein, M.; Haas, M.; Pozo Nuñez, F.; Murphy, M.
Abstract We present a first overview of variable stars in the Bochum Galactic Disk Survey (GDS) with emphasis on eclipsing binaries (EBs). This ongoing survey is performed by a robotic twin refractor at the Universitätssternwarte Bochum located near Cerro Armazones in Chile. It comprises a mosaic of 268 fields in a stripe of Δb = ±3° along the Galactic plane observed once per month simultaneously in the Sloan r and i filters with a detection limit of rs ∼ 16 mag and is ∼ 15 mag. The data from the first three years until the end of February 2014 yields a total of 41718 variable stars with variability amplitudes between 0.1–6 mag. A cross‐match with SIMBAD identified 11 465 of these variables unambiguously, while 2184 had multiple matches; most of the remaining stars could be matched with 2MASS objects. Among the SIMBAD‐listed objects with single matches, only 1982 turned out as known variables while a further 256 are suspected of variability. That leaves a total of 39480 potentially new variables. The group of known variables comprises 419 stars (21 %) that are classified as EBs while 443 (22%) are of other types; for the remaining 1120 catalogued variables (57 %) the type is unknown. Investigating variability as a function of spectral type, we find that SIMBAD provides spectral types for 2811 (25 %) of the identified stars. Spectral classes B (26 %), A (20 %), and M (25%) contain the most numerous variables, while all other classes contribute less than 10% each. More than half of the B (55 %) and A (56%) stars are designated as EBs, suggesting that hundreds of new B‐ and A‐type EBs may be contained in the GDS archive. In contrast, among the numerous M stars no EBs are known. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)